2007
DOI: 10.1074/jbc.m703513200
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-angiogenic Cytokine Pleiotrophin Potentiates Cardiomyocyte Apoptosis through Inhibition of Endogenous AKT/PKB Activity

Abstract: Pleiotrophin is a development-regulated cytokine and growth factor that can promote angiogenesis, cell proliferation, or differentiation, and it has been reported to have neovasculogenic effects in damaged heart. Developmentally, it is prominently expressed in fetal and neonatal hearts, but it is minimally expressed in normal adult heart. Conversely, we show in a rat model of myocardial infarction and in human dilated cardiomyopathy that pleiotrophin is markedly up-regulated. To elucidate the effects of pleiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
(46 reference statements)
3
29
0
3
Order By: Relevance
“…PTN shows both cytoplasmic (red arrows) and nuclear (black arrows) localization (brown staining), with the latter being dominant. Although there is no known physiological significance for the nuclear localization of PTN, it has been also observed in endothelial and glioma cells [78], cardiomyocytes [91] and osteoarthritic chondrocytes [9]. (For interpretation of the references to color in this text, the reader is referred to the web version of the article.)…”
Section: Discussionmentioning
confidence: 96%
“…PTN shows both cytoplasmic (red arrows) and nuclear (black arrows) localization (brown staining), with the latter being dominant. Although there is no known physiological significance for the nuclear localization of PTN, it has been also observed in endothelial and glioma cells [78], cardiomyocytes [91] and osteoarthritic chondrocytes [9]. (For interpretation of the references to color in this text, the reader is referred to the web version of the article.)…”
Section: Discussionmentioning
confidence: 96%
“…Although involvement of PTN in cardiac hypertrophy has not been extensively studied, our data are in line with a previous observation that PTN is increased in cardiac hypertrophy observed in atrial natriuretic peptide-null mice demonstrated at baseline or after transverse aortic constriction. 27 PTN has been also shown to potentiate cardiomyocyte cell death in response to proapoptotic stress in damaged heart that may be critical to myocardial injury repair 28 and PTN gene delivery leads to functional benefit in ischemic myocardium. 29 It is possible that PTN expression is affected by and/ or compensates decreased expression of VEGF or plays an independent role that requires further studies to be identified.…”
Section: Discussionmentioning
confidence: 98%
“…Promoter analysis revealed the existence of a CAAT box, no apparent TATA box, a serum response element, four MyoD, two putative AP1 and one GT1 binding sites in the distal 5' flanking region [12]. Moreover, it has been shown that hypoxia [13,14], PDGF [13] and cAMP [15] increase PTN expression, although the mechanisms involved are not known. It has been shown that PTN promoter contains a response element to HOXA5, which leads to increased PTN production [16].…”
Section: Gene Regulationmentioning
confidence: 99%
“…It is also important for clonal growth and long-term expansion of human embryonic stem cells [19]. More recently it has been shown to potentiate cardiomyocyte apoptosis and foster cardiomyocyte programmed cell death in response to proapoptotic stress, which may be critical to myocardial injury repair [14].…”
Section: Biological Activitiesmentioning
confidence: 99%